Analysis of Green Technology Development in Kazakhstan - Abdildin, Yerkin G.; Nurkenov, Serik A.; Kerimray, Aiymgul (International Journal of Energy Economics and Policy, 2021)
Although Kazakhstan is a fossil fuel rich country, there is a strong desire by policymakers to develop a green and sustainable economy and contribute to the global energy transition. To understand the overall situation in green technology development in industrial sector, we conducted the first countrywide study in Kazakhstan. In this paper, we present the results of the large survey on the use of ‘green technologies’ by industrial companies in every region of the country. We aggregate the 380 reported cases of the use of green technologies by sectors, like energy production, waste management, and some others. We found that the largest number of cases is accumulated in the waste management sector, the smallest, in green building construction. Our work shows that only 266 out of 877 ( 30%) industrial organizations in Kazakhstan utilize some form of green technologies. Based on detailed analysis of 141 organizations, Karagandy, East Kazakhstan, Aktobe, and Atyrau regions reported the largest number applications of green technologies among the 17 administrative-territorial units of Kazakhstan. We also discuss barriers to the diffusion of clean technologies. We believe that this work will be of interest to politicians, environmentalists, and practitioners who are concerned about the impacts of global warming. Keywords: clean technologies; sustainability; green economy; energy transition; power sector; climate change JEL Classifications: Q01, Q2, Q53, Q55, Q56, O33 DOI: https://doi.org/10.32479/ijeep.10897